2020
DOI: 10.3390/ijerph17103639
|View full text |Cite
|
Sign up to set email alerts
|

Welsh Primary Schoolchildren’s Perceptions of Electronic Cigarettes: A Mixed Methods Study

Abstract: There are concerns that the growing popularity of e-cigarettes promotes experimentation among children. Given the influence of the early years on attitude and habit formation, better understanding of how younger children perceive vaping before experimentation begins is needed, to prevent uptake and inform tobacco control strategies. We explored Welsh primary schoolchildren’s (aged 7–11) awareness of e-cigarettes relative to tobacco smoking, their understanding of the perceived risks and benefits and their inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…However, contrary to previous findings, no notable differences were identified here between pupils by age across years 4 to 6, contrasting with previous findings. 25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, contrary to previous findings, no notable differences were identified here between pupils by age across years 4 to 6, contrasting with previous findings. 25…”
Section: Discussionmentioning
confidence: 99%
“…The same study also suggested strong disapproval of smoking or vaping by young people, but greater levels of approval of both behaviours when done by adults. 25 UK schools provide education on smoking harms from a young age through programmes such as SchoolBeat in Wales (https://schoolbeat.cymru/); however, e-cigarettes are not featured in current recommendations and how or whether their use has been incorporated into teaching and school policies and practices is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…61 There is some evidence from the UK that finds that children see tobacco and e-cigarettes as distinct products. 62,63 In one study, for example, young people whose parents used e-cigarettes were most likely to perceive them as things adults use to stop smoking, with this perception of e-cigarettes as cessation aids associated with lower smoking susceptibility. 64 Hence, where perceived as stop smoking aids, others' use of e-cigarettes might be interpreted by young people as a social display of efforts to give up smoking, rather than as an endorsement of a smoking-like behaviour.…”
Section: The Renormalisation Hypothesismentioning
confidence: 99%
“…There are concerns that the growing popularity of e-cigarettes promotes tobacco experimentation, particularly among younger children 12 . A Welsh study of primary schoolchildren found that children as young as 7 years have general awareness of e-cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…A Welsh study of primary schoolchildren found that children as young as 7 years have general awareness of e-cigarettes. They perceived vaping to be healthier than smoking, had some recognition that e-cigarettes were used for smoking cessation but showed limited understanding of any health harms 12 .…”
Section: Introductionmentioning
confidence: 99%